The Concept, Practice, Application, and Results of Locally Based Monitoring of the Environment. (28th April 2021) - Danielsen, Finn; Enghoff, Martin; Poulsen, Michael K; Funder, Mikkel; Jensen, Per M; Burgess, Neil D
Abstract: Locally based monitoring is typically undertaken in areas in which communities have a close attachment to their natural resource base. We present a summary of work to develop a theoretical and practical understanding of locally based monitoring and we outline tests of this approach in research and practice over the past 20 years. Our tests show that locally based monitoring delivers credible data at local scale independent of external experts and can be used to inform local and national decision making within a short timeframe. We believe that monitoring conducted by and anchored in communities will gain in importance where scientist-led monitoring is sparse or too expensive to sustain and for ecosystem attributes in cases in which remote sensing cannot provide credible data. The spread of smartphone technology and online portals will further enhance the importance and usefulness of this discipline.